Epidemiological profile of infants with cleft lip and palate: a speech-language pathology perspective (Research, Society and Development, 2022)
Objective: To characterize the epidemiological profile of infants with cleft lip and palate. Methodology: This research is an observational, descriptive, retrospective, cross-sectional, analytical and quantitative epidemiological study carried out in a Public Maternity Hospital in the city of Joinville. The study was conducted by reviewing the medical records of patients with cleft lip and palate. All patients with cleft lip and palate, non-syndromic, of both sexes, born in a public maternity hospital from January 2015 to August 2021 participated in the study. A form containing information about sociodemographic and perinatal data was used for data collection. of the infant with cleft lip and palate, the type of cleft, anatomical location, form of feeding at discharge from the maternity hospital, antenatal diagnosis, number of prenatal consultations and occurrence of speech therapy stimulation. Results: From January 2015 to August 2021, 31 unborn children had isolated congenital cleft lip and palate. The prevalent type of cleft was unilateral left incisor transforamen, followed by incisive post-foramen. The form of feeding at discharge involved the use of adapters in the feeding, that is, a bottle utensil (48.4%) and mixed breastfeeding with a supplement in the bottle (29.0%). Of these 31 unborn children with cleft lip and palate, 30 (96.8%) received speech therapy (myofunctional stimulation). Conclusion: Based on the data obtained, the present study clarified that the prevalent mode of delivery of neonates with congenital cleft lip and palate was cesarean section and indicated that unborn children with cleft lip and palate are born adequate for their gestational age.